Investigating grit variables and their relations with practice and skill groups in developing sport experts - Tedesqui, R. A.; Young, B. W. (High Ability Studies, 2017)
Grit, the tendency to work hard toward long-term goals, maintaining effort and interest over years despite failure and adversity, has predicted several achievement outcomes. However, minimal work has examined grit within a sport expertise development framework, and specifically its association with deliberate practice (DP) in sport. Participants, 250 athletes (109 female; Mage = 23.40, SD = 10.14), completed the 12-item Grit Scale, practice measures, and reported their skill level (local to international). Factor analyses confirmed a 10-item two-factor model for use in our sport sample: consistency of interests (CI; 6 items; alpha = .81) and perseverance of effort (PE; 4 items; alpha = .75). A full latent variable model controlling for age showed PE significantly predicted weekly amounts of DP and engagement in mandatory and optional practice contexts; CI was inversely associated with threats to athletes` sport commitment. Among senior athletes, both Expert and Advanced skill groups had higher PE levels than a Basic/Intermediate group, ps < .05. The tendency to work hard toward long-term goals seemingly enables athletes to persist with practice activities that are pivotal to expert sport development.